Bridge expansion device based on alkali-activated high-strength concrete

By using alkali to stimulate high-strength concrete and C-shaped steel expansion joint components in the bridge expansion device, the installation process is simplified, the problems of complex installation and environmental pollution in the prior art are solved, and efficient and environmentally friendly bridge expansion device installation is achieved.

CN119287769APending Publication Date: 2025-01-10FUJIAN TRANSPORTATION PLANNING & DESIGN INST CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411423160.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The installation process of existing bridge expansion devices is complicated, which can easily damage the embedded steel bars, and the concrete surface is uneven, resulting in cracks and peeling in the anchorage area, which has a long installation cycle and affects transportation.

Method used

The bridge expansion device based on alkali-excited high-strength concrete is adopted, combined with embedded steel bars and C-shaped steel expansion joint components, and the high compressive strength and early condensation characteristics of high-strength concrete are stimulated through alkali, simplifying the installation process, and reducing environmental pollution by using industrial by-products such as slag .

Benefits of technology

It realizes a fast and simple installation process, improves anchoring strength and connection reliability, shortens construction cycle, reduces environmental pollution, and extends the service life of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287769A_ABST
    Figure CN119287769A_ABST
Patent Text Reader

Abstract

The invention provides a bridge expansion device based on alkali-activated high-strength concrete, which comprises embedded steel bars, alkali-activated high-strength concrete, C-shaped steel expansion joint members and waterstops, the lower ends of the embedded steel bars are embedded on bridge bodies at two ends of an expansion joint, the alkali-activated high-strength concrete is arranged on the bridge bodies, and the C-shaped steel expansion joint members are arranged on the waterstops. The upper ends of the embedded steel bars are embedded in the alkali-activated high-strength concrete on the corresponding side; the C-shaped steel expansion joint component comprises two C-shaped steel expansion joint component units, the rear ends of the two C-shaped steel expansion joint component units are connected to the corresponding embedded steel bars, the C-shaped steel expansion joint component units are embedded in the alkali-activated high-strength concrete, connecting openings in the front ends of the two C-shaped steel expansion joint component units are oppositely arranged, and the two ends of the water stop belt are embedded in the corresponding connecting openings respectively. The C-shaped steel expansion joints and the embedded steel bars can be poured only through lap joint and binding, and construction is simple and efficient; the alkali-activated high-strength concrete is short in setting time and high in early strength, the site construction period can be shortened, and the purpose of rapid traffic is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The invention relates to the technical field of bridge erection, and in particular to a bridge expansion device based on alkali-activated high-strength concrete. [Background technology]

[0002] The bridge expansion device is one of the important connecting components in the bridge structure. It can not only meet the needs of bridge expansion and displacement, but also enable vehicles to pass through the bridge deck smoothly, ensuring driving safety and comfort. In bridge engineering applications, the expansion device directly bears the repeated impact of wheel loads and is exposed to the atmosphere for a long time. The use environment is relatively harsh. At the same time, it must adapt to various complex displacement movements of the bridge. It is one of the parts of the bridge structure that is easily damaged and difficult to repair. It is a "hard nut to crack" problem in transportation construction management.

[0003] The on-site installation of existing bridge expansion devices is to reserve installation notches on both sides of the bridge joint in advance, and set embedded steel bars at the installation notches. When the bridge expansion device is to be installed, the asphalt and temporary fillers at the installation notches are cut and removed according to the notch size, and then the expansion device is hoisted into the expansion joint notch for positioning welding, and finally concrete is poured in the expansion joint notch. The concrete is cured for about seven days before it can be opened to traffic.

[0004] The shortcomings of the existing bridge expansion device and installation method are:

[0005] (1) It is troublesome to clean the installation notch, which often damages the original embedded steel bars, and debris easily falls off the beam end;

[0006] (2) The concrete surface is uneven and there is a serious misalignment with the bridge deck pavement. Under the impact load of traffic, tensile stress cracks are generated, causing the concrete anchoring area of ​​the telescopic device to crack and peel off;

[0007] (3) The damage to the expansion joint beam support element aggravates the impact on the expansion joint. At the same time, the maintenance is not in place and the expansion joint is not repaired in time, causing the steel components of the expansion device (special-shaped steel, etc.) to break;

[0008] (4) The position and size deviation of the embedded steel bars are large and cannot be directly welded to the telescopic device, which affects the anchoring strength of the telescopic device;

[0009] (5) The installation period is long, the process is complicated, and it requires long-term traffic interruption, which seriously affects the construction work of the bridge deck intersection. [Summary of the invention]

[0010] The technical problem to be solved by the present invention is to provide a bridge expansion device based on alkali-activated high-strength concrete to overcome the above-mentioned deficiencies in the prior art.

[0011] The present invention is achieved in that:

[0012] A bridge expansion device based on alkali-activated high-strength concrete, the bridge expansion device is arranged at the expansion joint of the bridge beam body, the bridge expansion device comprises pre-embedded steel bars, alkali-activated high-strength concrete, C-shaped steel expansion joint components and water stop strips, the lower end of each pre-embedded steel bar is embedded in the bridge beam body at both ends of the expansion joint, the alkali-activated high-strength concrete is arranged on the bridge beam body, and the upper end of the pre-embedded steel bar is embedded in the alkali-activated high-strength concrete on the corresponding side;

[0013] The C-shaped steel expansion joint component comprises two C-shaped steel expansion joint component units, the rear end of each C-shaped steel expansion joint component unit is connected to the corresponding embedded steel bar, and each C-shaped steel expansion joint component unit is buried in the alkali-activated high-strength concrete, and the front end of each C-shaped steel expansion joint component unit is provided with a connecting port, the two connecting ports are arranged opposite to each other and face one side of the expansion joint, and the two ends of the water stop are respectively embedded in the corresponding connecting ports;

[0014] The mass mix ratio of the alkali-activated high-strength concrete material is as follows: the gel material component adopts the ratio of slag: silica fume: fly ash=80:20-10:0-10, the water-binder ratio is 0.28-0.35, the mortar-sand ratio is 1.20-1.45, the water glass content is 18-22%, the modulus is 1.1-1.7, the steel fiber content is 0.5-1%, the water reducer is 1.4-1.6%, and the retarder is 1.8-2.2%;

[0015] The alkali-activated high-strength concrete has a 3-day compressive strength of more than 70 MPa.

[0016] A further technical solution is that a buffer baffle is arranged between the alkali-activated high-strength concrete and the asphalt layer at the rear side thereof.

[0017] Its further technical solution is: each of the C-shaped steel expansion joint component units includes a C-shaped steel fixing part and a fixed steel bar, the front end of the C-shaped steel fixing part is provided with a connecting port, the rear end of the C-shaped steel fixing part is fixedly connected to one end of the fixed steel bar, and the other end of the fixed steel bar is tied to the corresponding embedded steel bar.

[0018] A further technical solution is that the water stop strip is arranged along the entire length of the bridge expansion joint.

[0019] A further technical solution is that the water stop strip is made of polymer material or metal material.

[0020] A further technical solution is that the steel fiber is a straight cold-drawn copper-plated fiber with a diameter of 0.2 mm and two lengths of 6 mm and 13 mm.

[0021] A further technical solution is that the retarder is a composite retarder.

[0022] Its further technical scheme is: the mix ratio of the alkali-activated high-strength concrete material is: the gel material component adopts slag: silica fume: fly ash = 80:15:5 ratio, the water-cement ratio is 0.31, the mortar-sand ratio is 1.39, the water glass content is 20%, the modulus is 1.3, the steel fiber content is 1%, the water reducer is 1.5%, and the retarder is 2%; the retarder is a composite retarder of barium chloride and sodium gluconate.

[0023] The further technical solution is: the slag is S95 grade ore powder, and its density is 3.10g / cm 3 , fluidity is 98%, activity index 7d is 84.2%, 28d is 98.5%, specific surface area is 429m 2 / kg 3 , the burning vector is 0.84%, and the water content is 0.45%. The main chemical components of the slag are: SiO2 accounts for 34.5%, CaO accounts for 34%, Al2O3 accounts for 17.7%, MgO accounts for 6.01%, SO3 accounts for 1.64%, and Fe2O3 accounts for 1.03%;

[0024] The main chemical components of the silica fume are as follows: SiO2 is 93.80%, Al2O3 is 0.54%, Fe2O3 is 0.12%, CaO is 0.13%, MgO is 0.48%, K2O is 1.19%, Na2O is 0.50%, TiO2 is 0.21%, and LOI is 2.93%;

[0025] The main chemical components of the fly ash are: SiO2 is 53.97%, Al2O3 is 31.15%, Fe2O3 is 4.16%, CaO is 4.01%, K2O is 2.04%, TiO2 is 1.13%, MgO is 1.01%, Na2O is 0.89%, SO3 is 0.73%, P2O5 is 0.67%, Cl is 0.13%, and NiO is 0.11%.

[0026] The further technical solution is: the alkali activator is sodium silicate water glass, and its performance indicators are: solid content is 43.5, pH value is 10-13;

[0027] The water reducer is a polycarboxylic acid high-performance water reducer, and its performance parameters are: water reduction rate ≥ 25%, chloride ion content ≤ 0.6%, total alkali content ≤ 10, density 1.06g / cm3, pH value 5.0, sodium sulfate content ≤ 5.0, and solid content 38%.

[0028] The present invention has the following advantages:

[0029] The C-shaped steel expansion joint component provided by the present invention can be tied and overlapped on the pre-embedded steel bars of the beam body, and further anchored by alkali-activated recycled concrete. The construction is simple and efficient and the reliability of the connection is ensured. The assembled installation can be quickly carried out at the installation site of the expansion device, which greatly shortens the installation period of the expansion device and does not affect the bridge deck intersection construction. It solves the technical problem that the traditional expansion device has a long installation period and seriously affects the bridge deck intersection construction, and provides convenience for the later maintenance and repair work.

[0030] The alkali-activated high-strength concrete of the present invention can effectively utilize industrial by-product slag, and has simple industrial production, low energy consumption, low natural resource consumption, and low carbon dioxide emissions (about 10% of ordinary Portland cement emissions), which can greatly reduce the pollution to the environment during the entire production and construction process. The alkali-activated high-strength concrete has a 3-day compressive strength of more than 70MPa, a 28-day compressive strength of 120.66MPa, a tensile strength of 19.15MPa, and an elastic modulus of 42.56GPa. It has the characteristics of early strength and high strength, and also has a high ability to resist deformation. In actual engineering, it can shorten the construction period to a certain extent and improve construction efficiency.

[0031] In summary, the C-shaped steel expansion joint and the embedded steel bars of the present invention can be cast by simply overlapping and tying, and have the characteristics of simple and efficient construction; the alkali-activated high-strength concrete of the present invention has a fast setting time and high early strength, and can be put into use quickly, reducing the on-site construction cycle and achieving the purpose of rapid traffic. The alkali-activated high-strength concrete of the present invention has the characteristics of high strength, high fluidity, low carbon emission and fatigue resistance, which can fundamentally solve the problems of damage to expansion joints caused by various reasons, repeated repairs, etc., and has practical application value.

Brief Description of the Drawings

[0032] The present invention will be further described below in conjunction with embodiments with reference to the accompanying drawings.

[0033] Figure 1 This is a schematic diagram of a bridge expansion device based on alkali-activated high-strength concrete according to the present invention.

[0034] Figure 2 It is a schematic diagram of paving asphalt pavement during the construction of a bridge expansion device based on alkali-activated high-strength concrete according to the present invention.

[0035] Figure 3 It is a schematic diagram of cutting grooves and cleaning seams during the construction of a bridge expansion device based on alkali-activated high-strength concrete according to the present invention.

[0036] Figure 4 It is a schematic diagram of positioning and tying overlapping C-shaped steel expansion joint components during the construction of a bridge expansion device based on alkali-activated high-strength concrete according to the present invention.

[0037] Figure 5 The present invention is a schematic diagram of pouring alkali-activated high-strength concrete during the construction of a bridge expansion device based on alkali-activated high-strength concrete.

[0038] Description of reference numerals:

[0039] 1-embedded steel bars; 2-alkali-activated high-strength concrete; 3-C-shaped steel expansion joint component; 31-C-shaped steel expansion joint component unit; 311-connection port; 312-C-shaped steel fixing piece; 313-fixed steel bars; 4-waterstop; 5-buffer baffle;

[0040] 10-bridge beam; 20-expansion joint; 30-asphalt layer; 40-temporary baffle. [Specific implementation method]

[0041] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.

[0042] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0043] See also Figure 1-5 The present invention relates to a bridge expansion device based on alkali-activated high-strength concrete, the bridge expansion device is arranged at the expansion joint 20 of the bridge beam 10, the bridge expansion device comprises embedded steel bars 1, alkali-activated high-strength concrete 2, C-shaped steel expansion joint components 3 and water stop strips 4, the lower ends of the embedded steel bars 1 are embedded in the bridge beam 10 at both ends of the expansion joint, the alkali-activated high-strength concrete 2 is arranged on the bridge beam 10, and the upper ends of the embedded steel bars 1 are embedded in the alkali-activated high-strength concrete 2 on the corresponding side;

[0044] The C-shaped steel expansion joint component 3 includes two C-shaped steel expansion joint component units 31, the rear end of each C-shaped steel expansion joint component unit 31 is connected to the corresponding embedded steel bar 1, and each C-shaped steel expansion joint component unit 31 is buried in the alkali-activated high-strength concrete 2, and the front end of each C-shaped steel expansion joint component unit 31 is provided with a connecting port 311, the two connecting ports 311 are arranged opposite to each other and face one side of the expansion joint 20, and the two ends of the water stop 4 are respectively connected to the corresponding connecting ports 311;

[0045] The mix ratio of the alkali-activated high-strength concrete material is as follows: the gel material component adopts the ratio of slag: silica fume: fly ash = 80:15:5, the water-binder ratio is 0.31, the mortar-sand ratio is 1.39, the water glass content is 20%, the modulus is 1.3, the steel fiber content is 1%, the water reducer is 1.5%, and the retarder is 2%; the retarder is a composite retarder of barium chloride and sodium gluconate;

[0046] The slag is S95 grade ore powder with a density of 3.10 g / cm 3 , fluidity is 98%, activity index 7d is 84.2%, 28d is 98.5%, specific surface area is 429m 2 / kg 3 , the burning vector is 0.84%, and the water content is 0.45%. The main chemical components of the slag are: SiO2 accounts for 34.5%, CaO accounts for 34%, Al2O3 accounts for 17.7%, MgO accounts for 6.01%, SO3 accounts for 1.64%, and Fe2O3 accounts for 1.03%;

[0047] The main chemical components of the silica fume are as follows: SiO2 is 93.80%, Al2O3 is 0.54%, Fe2O3 is 0.12%, CaO is 0.13%, MgO is 0.48%, K2O is 1.19%, Na2O is 0.50%, TiO2 is 0.21%, and LOI is 2.93%;

[0048] The main chemical components of the fly ash are as follows: SiO2 is 53.97%, Al2O3 is 31.15%, Fe2O3 is 4.16%, CaO is 4.01%, K2O is 2.04%, TiO2 is 1.13%, MgO is 1.01%, Na2O is 0.89%, SO3 is 0.73%, P2O5 is 0.67%, Cl is 0.13%, and NiO is 0.11%;

[0049] The alkaline activator is sodium silicate water glass, and its performance indicators are: solid content is 43.5, pH value is 10-13;

[0050] The water reducer is a polycarboxylic acid high-performance water reducer, and its performance parameters are: water reduction rate ≥ 25%, chloride ion content ≤ 0.6%, total alkali content ≤ 10, density 1.06g / cm3, pH value 5.0, sodium sulfate content ≤ 5.0, solid content 38%;

[0051] The alkali-activated high-strength concrete has a 3-day compressive strength of more than 70 MPa.

[0052] In a specific implementation, a preferred embodiment is as follows: a buffer baffle 5 is provided between the alkali-activated high-strength concrete 2 and the asphalt layer 30 at its rear side. The buffer baffle 5 can buffer and disperse the impact load transmitted from the asphalt layer 30, reduce the impact on the bridge expansion device during vehicle driving, and improve the service life of the bridge expansion device.

[0053] In a specific implementation, a preferred embodiment is as follows: each of the C-shaped steel expansion joint component units 31 includes a C-shaped steel fixing part 312 and a fixed steel bar 313, the front end of the C-shaped steel fixing part 312 is provided with a connecting port 311, the rear end of the C-shaped steel fixing part 312 is fixedly connected to one end of the fixed steel bar 313, and the other end of the fixed steel bar 313 is tied to the corresponding embedded steel bar 1.

[0054] In a specific implementation, a preferred embodiment is as follows: the water stop strip 4 is arranged along the entire length of the bridge expansion joint 20 .

[0055] In a specific implementation, a preferred embodiment is: the water stop strip 4 is made of polymer material or metal material.

[0056] In a specific implementation, a preferred embodiment is as follows: the steel fiber is a straight cold-drawn copper-plated fiber with a diameter of 0.2 mm and two lengths of 6 mm and 13 mm.

[0057] In a specific implementation, a preferred embodiment is: the retarder is a composite retarder.

[0058] See also Figure 2-5 In another embodiment of the present invention, the installation method of the bridge expansion device based on alkali-activated high-strength concrete is as follows: in the early stage of the bridge beam 10 construction, the steel bars 1 are pre-embedded, and in the later stage of the assembled installation construction of the expansion device, the C-shaped steel expansion joint components 3 are tied and overlapped, and then the alkali-activated high-strength concrete 2 can be poured; the construction method includes the following steps:

[0059] A. Requirements for pre-embedded steel bars and paving of bridge beams in the early stage:

[0060] A1. Embed steel bars when prefabricating or casting the beam;

[0061] A2. The gap at the beam end is temporarily covered with a temporary baffle 40, and then the asphalt pavement is paved to ensure that the thickness of the asphalt pavement is uniform.

[0062] B. Assembly installation of telescopic device:

[0063] B1. Draw lines, cut grooves, and clean seams: Draw the installation groove position line according to the dimensions of the construction drawing, cut the asphalt pavement along the drawn line according to the bridge deck pavement depth, and clean the asphalt and debris in the installation groove.

[0064] B2. Install the expansion device: tie and overlap the C-shaped steel expansion joint component 3 and the embedded steel bar 1.

[0065] B3. Pour alkali-activated high-strength concrete 2 and fix the waterproof device: After the overlap is completed, the alkali-activated high-strength concrete 2 can be poured, and the C-shaped steel fixings 312 are fixed in place before it solidifies. The waterstop strip 4 is embedded in the C-shaped steel fixings 312 of the C-shaped steel expansion joint component 3 to prevent rainwater from flowing from the bottom of the C-shaped steel expansion joint component 3 to the beam end, and the alkali-activated high-strength concrete 2 is cured.

[0066] The technical solution of the present invention will be clearly and completely described below in conjunction with the specific implementation methods of alkali-activated high-strength concrete. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0067] Example 1

[0068] The mix ratio of the alkali-activated high-strength concrete material is as follows: the gel material component adopts the ratio of slag: silica fume: fly ash = 80:15:5, the water-binder ratio is 0.31, the mortar-sand ratio is 1.39, the water glass content is 20%, the modulus is 1.3, the steel fiber content is 1%, the water reducer is 1.5%, and the retarder is 2%;

[0069] The slag is S95 grade ore powder with a density of 3.10 g / cm 3 , fluidity is 98%, activity index 7d is 84.2%, 28d is 98.5%, specific surface area is 429m 2 / kg 3 , the burning vector is 0.84%, and the water content is 0.45%. The main chemical components of the slag are: SiO2 accounts for 34.5%, CaO accounts for 34%, Al2O3 accounts for 17.7%, MgO accounts for 6.01%, SO3 accounts for 1.64%, and Fe2O3 accounts for 1.03%;

[0070] The main chemical components of the silica fume are as follows: SiO2 is 93.80%, Al2O3 is 0.54%, Fe2O3 is 0.12%, CaO is 0.13%, MgO is 0.48%, K2O is 1.19%, Na2O is 0.50%, TiO2 is 0.21%, and LOI is 2.93%;

[0071] The main chemical components of the fly ash are as follows: SiO2 is 53.97%, Al2O3 is 31.15%, Fe2O3 is 4.16%, CaO is 4.01%, K2O is 2.04%, TiO2 is 1.13%, MgO is 1.01%, Na2O is 0.89%, SO3 is 0.73%, P2O5 is 0.67%, Cl is 0.13%, and NiO is 0.11%;

[0072] The alkaline activator is sodium silicate water glass, and its performance indicators are: solid content is 43.5, pH value is 10-13;

[0073] The water reducer is a polycarboxylic acid high-performance water reducer, and its performance parameters are: water reduction rate ≥ 25%, chloride ion content ≤ 0.6%, total alkali content ≤ 10, density 1.06g / cm3, pH value 5.0, sodium sulfate content ≤ 5.0, solid content 38%;

[0074] The steel fiber is a straight cold-drawn copper-plated fiber with a diameter of 0.2 mm and a length of a mixture of 6 mm and 13 mm. The retarder is a composite retarder.

[0075] The alkali-activated high-strength concrete prepared above has a concrete fluidity of 190 mm, a compressive strength of more than 70 MPa in 3 days, a compressive strength of 120.66 MPa in 28 days, a tensile strength of 19.15 MPa, and an elastic modulus of 42.56 GPa. It has the characteristics of early strength and high strength, and also has a high ability to resist deformation. The initial setting time is 15 minutes. In actual projects, it can shorten the construction period to a certain extent and improve the construction efficiency.

[0076] Example 2

[0077] The mix ratio of the alkali-activated high-strength concrete material is as follows: the gel material component adopts the ratio of slag: silica fume: fly ash = 80:20:0, the water-binder ratio is 0.31, the mortar-sand ratio is 1.39, the water glass content is 20%, the modulus is 1.3, the steel fiber content is 1%, the water reducer is 1.5%, and the retarder is 2%;

[0078] The slag is S95 grade ore powder with a density of 3.10 g / cm 3 , fluidity is 98%, activity index 7d is 84.2%, 28d is 98.5%, specific surface area is 429m2 / kg 3 , the burning vector is 0.84%, and the water content is 0.45%. The main chemical components of the slag are: SiO2 accounts for 34.5%, CaO accounts for 34%, Al2O3 accounts for 17.7%, MgO accounts for 6.01%, SO3 accounts for 1.64%, and Fe2O3 accounts for 1.03%;

[0079] The main chemical components of the silica fume are as follows: SiO2 is 93.80%, Al2O3 is 0.54%, Fe2O3 is 0.12%, CaO is 0.13%, MgO is 0.48%, K2O is 1.19%, Na2O is 0.50%, TiO2 is 0.21%, and LOI is 2.93%;

[0080] The alkaline activator is sodium silicate water glass, and its performance indicators are: solid content is 43.5, pH value is 10-13;

[0081] The water reducer is a polycarboxylic acid high-performance water reducer, and its performance parameters are: water reduction rate ≥ 25%, chloride ion content ≤ 0.6%, total alkali content ≤ 10, density 1.06g / cm3, pH value 5.0, sodium sulfate content ≤ 5.0, solid content 38%;

[0082] The steel fiber is a straight cold-drawn copper-plated fiber with a diameter of 0.2 mm and a length of a mixture of 6 mm and 13 mm. The retarder is a composite retarder.

[0083] The alkali-activated high-strength concrete prepared above has a concrete fluidity of 181 mm, a 3-day compressive strength of more than 70 MPa, a 28-day compressive strength of 117.89 MPa, a tensile strength of 18.94 MPa, and an elastic modulus of 41.69 GPa. It has the characteristics of early strength and high strength, and also has a high ability to resist deformation. The initial setting time is 14 minutes. In actual projects, it can shorten the construction period to a certain extent and improve construction efficiency.

[0084] Example 3

[0085] The mix ratio of the alkali-activated high-strength concrete material is as follows: the gel material component adopts the ratio of slag: silica fume: fly ash = 80:10:10, the water-binder ratio is 0.31, the mortar-sand ratio is 1.39, the water glass content is 20%, the modulus is 1.3, the steel fiber content is 1%, the water reducer is 1.5%, and the retarder is 2%;

[0086] The slag is S95 grade ore powder with a density of 3.10 g / cm 3 , fluidity is 98%, activity index 7d is 84.2%, 28d is 98.5%, specific surface area is 429m 2 / kg3 , the burning vector is 0.84%, and the water content is 0.45%. The main chemical components of the slag are: SiO2 accounts for 34.5%, CaO accounts for 34%, Al2O3 accounts for 17.7%, MgO accounts for 6.01%, SO3 accounts for 1.64%, and Fe2O3 accounts for 1.03%;

[0087] The main chemical components of the silica fume are as follows: SiO2 is 93.80%, Al2O3 is 0.54%, Fe2O3 is 0.12%, CaO is 0.13%, MgO is 0.48%, K2O is 1.19%, Na2O is 0.50%, TiO2 is 0.21%, and LOI is 2.93%;

[0088] The main chemical components of the fly ash are as follows: SiO2 is 53.97%, Al2O3 is 31.15%, Fe2O3 is 4.16%, CaO is 4.01%, K2O is 2.04%, TiO2 is 1.13%, MgO is 1.01%, Na2O is 0.89%, SO3 is 0.73%, P2O5 is 0.67%, Cl is 0.13%, and NiO is 0.11%;

[0089] The alkaline activator is sodium silicate water glass, and its performance indicators are: solid content is 43.5, pH value is 10-13;

[0090] The water reducer is a polycarboxylic acid high-performance water reducer, and its performance parameters are: water reduction rate ≥ 25%, chloride ion content ≤ 0.6%, total alkali content ≤ 10, density 1.06g / cm3, pH value 5.0, sodium sulfate content ≤ 5.0, solid content 38%;

[0091] The steel fiber is a straight cold-drawn copper-plated fiber with a diameter of 0.2 mm and a length of a mixture of 6 mm and 13 mm. The retarder is a composite retarder.

[0092] The alkali-activated high-strength concrete prepared above has a concrete fluidity of 188 mm, a compressive strength of more than 70 MPa in 3 days, a compressive strength of 106.44 MPa in 28 days, a tensile strength of 15.88 MPa, and an elastic modulus of 39.84 GPa. It has the characteristics of early strength and high strength, and also has a high ability to resist deformation. The initial setting time is 16 minutes. In actual projects, it can shorten the construction period to a certain extent and improve construction efficiency.

[0093] In summary, the advantages of the present invention are as follows:

[0094] The C-shaped steel expansion joint component provided by the present invention can be tied and overlapped on the pre-embedded steel bars of the beam body, and further anchored by alkali-activated recycled concrete. The construction is simple and efficient and the reliability of the connection is ensured. The assembled installation can be quickly carried out at the installation site of the expansion device, which greatly shortens the installation period of the expansion device and does not affect the bridge deck intersection construction. It solves the technical problem that the traditional expansion device has a long installation period and seriously affects the bridge deck intersection construction, and provides convenience for the later maintenance and repair work.

[0095] The alkali-activated high-strength concrete of the present invention can effectively utilize industrial by-product slag, and has simple industrial production, low energy consumption, low natural resource consumption, and low carbon dioxide emissions (about 10% of ordinary Portland cement emissions), which can greatly reduce the pollution to the environment during the entire production and construction process. The alkali-activated high-strength concrete has a 3-day compressive strength of more than 70MPa, a 28-day compressive strength of 120.66MPa, a tensile strength of 19.15MPa, and an elastic modulus of 42.56GPa. It has the characteristics of early strength and high strength, and also has a high ability to resist deformation. In actual engineering, it can shorten the construction period to a certain extent and improve construction efficiency.

[0096] In summary, the C-shaped steel expansion joint and the embedded steel bars of the present invention can be cast by simply overlapping and tying, and have the characteristics of simple and efficient construction; the alkali-activated high-strength concrete of the present invention has a fast setting time and high early strength, and can be put into use quickly, reducing the on-site construction cycle and achieving the purpose of rapid traffic. The alkali-activated high-strength concrete of the present invention has the characteristics of high strength, high fluidity, low carbon emission and fatigue resistance, which can fundamentally solve the problems of damage to expansion joints caused by various reasons, repeated repairs, etc., and has practical application value.

[0097] Although the specific implementation modes of the present invention are described above, those skilled in the art should understand that the specific implementation modes described are only illustrative and are not intended to limit the scope of the present invention. Equivalent modifications and changes made by those skilled in the art in accordance with the spirit of the present invention should be included in the scope of protection of the claims of the present invention.

Claims

1. A bridge expansion device based on alkali-activated high-strength concrete, the bridge expansion device is arranged at the expansion joint of the bridge beam, characterized in that: The bridge expansion device includes embedded steel bars, alkali-activated high-strength concrete, C-shaped steel expansion joint components and water stop strips, the lower end of each embedded steel bar is embedded in the bridge beam at both ends of the expansion joint, the alkali-activated high-strength concrete is arranged on the bridge beam, and the upper end of the embedded steel bar is embedded in the alkali-activated high-strength concrete on the corresponding side; The C-shaped steel expansion joint component comprises two C-shaped steel expansion joint component units, the rear end of each C-shaped steel expansion joint component unit is connected to the corresponding embedded steel bar, and each C-shaped steel expansion joint component unit is buried in the alkali-activated high-strength concrete, and the front end of each C-shaped steel expansion joint component unit is provided with a connecting port, the two connecting ports are arranged opposite to each other and face one side of the expansion joint, and the two ends of the water stop are respectively embedded in the corresponding connecting ports; The mass mix ratio of the alkali-activated high-strength concrete material is as follows: the gel material component adopts the ratio of slag: silica fume: fly ash=80:20-10:0-10, the water-binder ratio is 0.28-0.35, the mortar-sand ratio is 1.20-1.45, the water glass content is 18-22%, the modulus is 1.1-1.7, the steel fiber content is 0.5-1%, the water reducer is 1.4-1.6%, and the retarder is 1.8-2.2%; The alkali-activated high-strength concrete has a 3-day compressive strength of more than 70 MPa.

2. The bridge expansion device based on alkali-activated high-strength concrete according to claim 1 is characterized by: A buffer baffle is arranged between the alkali-activated high-strength concrete and the asphalt layer at the rear side thereof.

3. The bridge expansion device based on alkali-activated high-strength concrete according to claim 1 is characterized by: Each of the C-shaped steel expansion joint component units includes a C-shaped steel fixing piece and a fixed steel bar. The front end of the C-shaped steel fixing piece is provided with a connecting port, the rear end of the C-shaped steel fixing piece is fixedly connected to one end of the fixed steel bar, and the other end of the fixed steel bar is tied to the corresponding embedded steel bar.

4. The bridge expansion device based on alkali-activated high-strength concrete according to claim 1 is characterized by: The water stop is arranged along the entire length of the bridge expansion joint.

5. The bridge expansion device based on alkali-activated high-strength concrete according to claim 1 is characterized by: The water stop strip is made of polymer material or metal material.

6. The bridge expansion device based on alkali-activated high-strength concrete according to claim 1 is characterized by: The steel fiber is a straight cold-drawn copper-plated fiber with a diameter of 0.2 mm and two lengths of 6 mm and 13 mm.

7. The bridge expansion device based on alkali-activated high-strength concrete according to claim 1 is characterized by: The retarder is a composite retarder.

8. The bridge expansion device based on alkali-activated high-strength concrete according to claim 1 is characterized by: The mass mix ratio of the alkali-activated high-strength concrete material is as follows: the gel material components adopt the ratio of slag: silica fume: fly ash = 80:15:5, the water-cement ratio is 0.31, the mortar-sand ratio is 1.39, the water glass content is 20%, the modulus is 1.3, the steel fiber content is 1%, the water reducer is 1.5%, and the retarder is 2%; the retarder is a composite retarder of barium chloride and sodium gluconate.

9. The bridge expansion device based on alkali-activated high-strength concrete according to claim 8, characterized in that: The slag is S95 grade ore powder, and its density is 3.10g / cm 3 , fluidity is 98%, activity index 7d is 84.2%, 28d is 98.5%, specific surface area is 429m 2 / kg 3 , the burning vector is 0.84%, and the water content is 0.45%. The main chemical components of the slag are: SiO2 accounts for 34.5%, CaO accounts for 34%, Al2O3 accounts for 17.7%, MgO accounts for 6.01%, SO3 accounts for 1.64%, and Fe2O3 accounts for 1.03%; The main chemical components of the silica fume are as follows: SiO2 is 93.80%, Al2O3 is 0.54%, Fe2O3 is 0.12%, CaO is 0.13%, MgO is 0.48%, K2O is 1.19%, Na2O is 0.50%, TiO2 is 0.21%, and LOI is 2.93%; The main chemical components of the fly ash are: SiO2 is 53.97%, Al2O3 is 31.15%, Fe2O3 is 4.16%, CaO is 4.01%, K2O is 2.04%, TiO2 is 1.13%, MgO is 1.01%, Na2O is 0.89%, SO3 is 0.73%, P2O5 is 0.67%, Cl is 0.13%, and NiO is 0.11%.

10. The bridge expansion device based on alkali-activated high-strength concrete according to claim 8, characterized in that: The alkaline activator is sodium silicate water glass, and its performance indicators are: solid content is 43.5, pH value is 10-13; The water reducer is a polycarboxylic acid high-performance water reducer, and its performance parameters are: water reduction rate ≥ 25%, chloride ion content ≤ 0.6%, total alkali content ≤ 10, density 1.06g / cm3, pH value 5.0, sodium sulfate content ≤ 5.0, and solid content 38%.

Citation Information

Patent Citations

  • Installation and construction process of bridge expansion joints

    CN102966037A

  • Bridge expansion joint device without transition section concrete and mounting method of bridge expansion joint device

    CN103741597A

  • Bridge expansion joint preformed notch of assembly type structure and construction method of bridge expansion joint preformed notches

    CN109853375A

  • Construction method for reserving bridge expansion joint

    CN113235437A

  • Construction structure of expansion joint and construction method of expansion joint

    CN114108455A